Emerging Knowledge, Attitudes and Practices In Response to The Novel Coronavirus in Nursing Students: An Online-Based Cross-Sectional Study - Fransiskus Xaverius Widiantoro; Yosi Maria Wijaya (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2021)
Introduction: The knowledge, attitudes, and practices (KAP) in response to Covid-19 have not been measured previously in nursing institutions, which could be crucial to preventing a second wave of the Covid-19 pandemic in Indonesia. This study examined the KAP for Covid-19 among Indonesian nursing students during the rapid increase period. Methods: An online-based cross-sectional design recruited nursing students using the authors’ networks with lecturers and nursing institutions in Indonesia. After obtaining their consent, the participants completed an online survey to assess their socio-demographic details, habits, family history of chronic diseases, and KAP in response to Covid-19. Simple descriptive through to complex analyses and multivariate regression were carried out using SPSS 17. Results: There were a total of 492 participants; 84.4% were female, most had a Bachelor’s degree (71.3%) and the mean age was 23.9 years old. The majority had never smoked (94.3%), drank warm water everyday (61.6%), exercised (50.6%), did not have hypertension (96.3%), had no family history of select conditions (79.9%) and had not been diagnosed with diabetes (99.4%). The majority of participants (79.3%) had good knowledge, where the mean for attitude was 2.05 (SD=0.30) and the result for practices was 2.19 (SD=0.42). Multiple linear regression showed that males who were older were associated with a higher level of knowledge. Conclusion: Our results found that the nursing students had good KAP scores regarding Covid-19. The development of effective health education programs to uphold their optimistic attitude and to maintain their good practices is needed.